Seismic Data Analysis to the Converted Wave Acquisition: A Case Study in Offshore Malaysia - ., AH Abdul Latiff, SAA Osman, SNF Jamaludin (2016)
Many fields in offshore Malaysia suffer from the presence of shallow gas cloud which is one of the major issues in the basin. Seismic images underneath the gas cloud often show poor resolution which makes the geophysical and geological interpretation difficult. This effect can be noticed from the amplitude dimming, loss of high-frequency energy, and phase distortion. In this work, the subsurface will be analyzed through the geophysical interpretation of the converted P-S data. This P-S converted dataset was obtained through ocean bottom cable (OBC) procedure which was conducted at a shallow gas affected field located in Malaysian Basin. The geophysical interpretation process begin by picking the clear faults system and horizons, followed by thorough post-stack seismic data processing procedure. Finally, the attributes analyses were implemented to the seismic section in order to image the unseen faults system. The interpreted seismic sections show significant improvement in the seismic images, particularly through median filter process. Moreover, the combination of structural smoothing and variance procedure had contributed to the correct faults location interpretation.